Tout cela est bien quelque chose: Digital Preservation Today: How European Commission programmes and policy have brought us here: Festschrift for Patricia (Pat) Manson - Delve, Janet; Anderson, David (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
Patricia (Pat) Manson worked with the European Commission's (EC’s) research programmes from the early 1990s, initially as project officer (December 1991-March 2003) and then as Head of Unit (April 2003-2011) for Cultural Heritage and Technology Enhanced Learning which was part of the Directorate General Information Society and Media. The unit focused primarily on research in digital libraries, digital preservation, and in the use of ICTs for improving learning, but was also involved in the development of the i2010 digital libraries policies and actions. Prior to joining the Commission, she worked in the UK providing a national advisory and market watch service to libraries on the use of new technologies. She is now Head of the Inclusion, Skills & Youth Unit of the EC’s Directorate General for Communication Networks, Content and Technology (DG CONNECT), where the unit’s goal is to ensure that citizens, especially youth and those at risk of exclusion, are best able to benefit from the Internet and have the necessary skills so to do. This article sets out Pat’s leadership of EC-funded Digital Preservation, and examines her legacy in terms of lasting best practices, contributions to standardisation activities etc.